2022
DOI: 10.3390/ijerph19074134
|View full text |Cite
|
Sign up to set email alerts
|

Food By-Product Valorization by Using Plant-Based Coagulants Combined with AOPs for Agro-Industrial Wastewater Treatment

Abstract: Re-using and adding value to by-products is one of the current focuses of the agri-food industry, following the Sustainable Development Goals of United Nations. In this work, the by-products of four plants, namely chestnut burr, acorn peel, olive leaf, and grape stem were used as coagulants to treat elderberry wastewater (EW), a problematic liquid effluent. EW pre-treatment using these natural coagulants showed promising results after pH and coagulant dosage optimization. However, the decrease in total organic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 42 publications
3
7
0
Order By: Relevance
“…The SEM images (Figure 1b) show that the almond skin powder presents dark spaces that correspond to empty spaces, similar to findings in other works involving plant-based materials [38]. These porous materials allow the adsorption of the NaCl solution and the desorption of material from the powder to the exterior, a necessary characteristic to produce the ASE.…”
Section: Characterization Of Almond Skin Powdersupporting
confidence: 83%
“…The SEM images (Figure 1b) show that the almond skin powder presents dark spaces that correspond to empty spaces, similar to findings in other works involving plant-based materials [38]. These porous materials allow the adsorption of the NaCl solution and the desorption of material from the powder to the exterior, a necessary characteristic to produce the ASE.…”
Section: Characterization Of Almond Skin Powdersupporting
confidence: 83%
“…In Table 1, the plants sub species, part collected for this study and the herbarium number attributed by UTAD for the plant's identification are shown. All the plant-based coagulants were prepared in accordance with Martins et al [4].…”
Section: Plant-based Coagulant Preparationmentioning
confidence: 99%
“…As a result, the use of chemical coagulants has been reduced, and the search for greener and equally efficient options has increased [16,17]. Although the use of plants as natural coagulants for water treatment is an ancestral technique, it has only recently been widely studied as an alternative environmentally friendly procedure to the use of chemical-based coagulants [17][18][19]. Natural coagulants are biodegradable, non-toxic, non-corrosive, and cheaper than chemical coagulants [17].…”
Section: Introductionmentioning
confidence: 99%